A molecular imprinting-based multifunctional chemosensor for phthalate esters. (February 2017) - Gong, Cheng-bin; Ou, Xiao-xiao; Liu, Song; Jin, Yong-lei; Huang, Hai-rong; Tang, Qian; Hon-Wah Lam, Michael; Chow, Cheuk-fai; Tang, Qian
Abstract: This paper reports a molecular imprinting-based fluorescent and solvatochromic multifunctional chemosensor for phthalate esters (PAEs). The multifunctional chemosensor was fabricated through precipitation polymerization using 4-[(1 E )-4-(2-hydroxyphenyl) ethenyl]-1-allylpyridinium bromide (HPEAPB) as the functional monomer and phthalamide-4, 4′-dibutyl dimethyl ester (PDDB) as the mimic template. The molecular imprinting-based chemosensor shows specific affinity toward PDDB and dibutyl phthalate (DBP) in ethanol. Of note is that the molecular imprinting-based chemosensor shows turn-off fluorescent response toward PAEs in an ethanol solution with a limit of detection of 2.0 × 10 −6  mol L -1 (0.7 ppm) when HPEAPB is in the protonated form (chemosensor 1), and shows solvatochromic properties, fluorescent enhancement and a colorimetric (from orange to bright yellow) response toward PAEs in an ethanol solution with a limit of detection of 4.0 × 10 −5  mol L -1  by the naked eye when HPEAPB is in the deprotonated form (chemosensor 2). This multifunctional chemosensor is promising for the simple, accurate and low-cost detection of trace PAEs. Graphical abstract: Highlights: Molecular imprinting-based fluorescent and solvatochromic chemosensor was synthesized. Chemosensor 1 exhibits a turn-off fluorescent response toward phthalate esters in ethanol. Chemosensor 2 shows solvatochromic properties. Chemosensor 2 displays fluorescent-enhancing and colorimetric response toward DBP.